When the Wind Blows: Exposing the Constraints of Drone‐Based Environmental Mapping - Jan Komárek (Natural Sciences)
ABSTRACT Drones have become indispensable for high‐resolution, on‐demand remote sensing, yet their valid operational window is far narrower than often portrayed. Using meteorological data from 31 locations in the Czech Republic since 2016, we demonstrate that weather constraints—including precipitation, wind and temperature extremes—collectively limit feasible flight days to roughly 25% per year. Although an overall 0.8°C rise in average temperature since 2019 has slightly reduced cold‐weather issues, it has introduced more frequent heatwaves and increased wind variability, offsetting potential gains. High wind gusts, precipitation and temperature can degrade sensor accuracy and distort imagery even when conditions permit flight. Radiometric data collection—often conducted near solar noon—can be disrupted by clouds, haze or gusts, complicating efforts to obtain consistent, high‐quality measurements. Despite these pervasive effects, many drone‐based studies lack detailed weather documentation, hindering data reproducibility and comparisons. Weather nowcasting and adaptive mission planning offer ways to mitigate data gaps, but questions remain about ensuring sustained, high‐quality coverage in variable climates. By acknowledging and addressing inherent weather constraints, the remote sensing community can more realistically harness drones’ potential and refine operational guidelines for long‐term environmental monitoring. Highlights: Meteorological constraints are a strong reality check. Climate trends alter but don't solve drone limitations. Future improvements must go beyond hardware enhancements.